Association between postoperative intravenous methylprednisolone and surgical site infection in posterior lumbar fusion surgery: a retrospective single-center study - Yuancheng Zhang; Jiahua Xie; Tianzuo Niu; Siping Deng; Jianru Wang; Hui Liu; Zemin Li (BMC Musculoskeletal Disorders)
Abstract Purpose To investigate the association between intravenous methylprednisolone administration and the risk of surgical site infection (SSI) following posterior lumbar fusion (PLF) surgery. Methods This retrospective, single-center study analyzed data from 800 adult patients who underwent elective PLF surgery at our institution. Patients were classified according to postoperative intravenous methylprednisolone administration. Univariate and multivariable logistic regression, and subgroup analysis were used to assess the association between methylprednisolone administration and SSI risk, as well as its impact on postoperative pain management. Results Our analysis showed no significant association between intravenous methylprednisolone administration and the development of a SSI after PLF. Subgroup analyses suggested that methylprednisolone was potentially protective in patients with a body mass index (BMI) < 25 kg/m2. In addition, patients treated with methylprednisolone had significantly lower pain scores in the early postoperative period, and lower incidence of postoperative nausea and vomiting (PONV) compared to patients not treated with methylprednisolone. However, there was no significant difference in pain scores between the 2 groups at 4 weeks postoperatively. Conclusions This study suggests that intravenous methylprednisolone administration may not increase the risk of SSI after single-level PLF. In addition, it appears to have a beneficial effect on postoperative pain management and PONV, especially during the early recovery phase.